Decomposition of Food Waste by using Vegetable Fermentation Solution - Mohd Hassan, Muhammad Nuraiman; Tuan Ismail, Tuan Noor Hasanah; Hashim, Nor Haslina; Hamidon, Nuramidah (Penerbit UTHM, 2020)
Food waste is an inevitable outcome of human consumption in modern society, it was happened in almost every home on a daily basis. The increasing amount of food waste in Malaysia caused by the fast growth of population and to meet the human lifestyle has become a major environmental issues in recent years. SWCorp (2016) reported that it was contributes the highest composition in municipal solid waste which is 44.5%. In 2015, Malaysians throw away of about 15,000 tonnes of food waste every day, about 3,000 tonnes are actually eatable and should not be dumped (Jarjusey & Chamhuri, 2017). In 2020, about 49,670 tons per day of waste is expected to be generated in Malaysians (Jabatan Pengurusan Sisa Pepejal Negara, 2012).